KEEFEKTIFAN MEDIA KOMIK TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS IV SD - Untari, Mei Fita Asri; Saputra, Aprilianta Adi (Mimbar Sekolah Dasar, 2016)
This research is motivated by the low reading interest of children who have an impact on learning outcome is low and the need to streamline the reading comprehension to be able easily understand the material being studied. This study aims to determine the effectiveness of the medium of comics to the students' reading ability. Based on the analysis of data, the first measurement using the story "Reaching Cita Although almost Despair" of 30 fourth-grade students of SDN 03 Bergaskidul Semarang District 25 students with learning outcome is high enough - and five students with poor outcomes. The average was 73.33. After being treated for the provision of comics, from 30 students of SDN 03 Bergaskidul Semarang regency, retrieved 29 students achieving grades with the criteria fairly high and only one students still have low criteria. The average value rose to 81.33. Percentage increase is 3.878%. The second measurement using the story "Cita-Citaku" of 30 fourth-grade students of SDN 03 Bergaskidul Semarang District, there are 14 students with learning outcome is high enough - and 16 students with poor outcomes. The average was 53.67. After being treated for the provision of comics, from 30 students of SDN 03 Bergaskidul Semarang regency, retrieved 22 students achieving grades with the criteria fairly high and eight students who still haveÂ low criteria. The average value rose to 66.67. Percentage increase is 2, 037%.Keywords: effectiveness, media comics, reading comprehension.